Pengaruh Penerapan Standart Akuntansi Pemerintah, Sistem Akuntansi Keuangan Daerah dan Kompetensi SDM Terhadap Kualitas Laporan Keuangan - Noor, Ikke Habibaty; Putuhena, Hempry (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The quality of financial reports will describe the responsibility and capabilities of companies and agencies. The government has set policies regarding financial reports, where ideal financial reports must meet government accounting standards, regional accounting systems, and competent human resources. So the purpose of the study is to see the influence of the application of government accounting standards, regional financial accounting systems and HR competencies on the quality of financial reports. The research method uses a quantitative approach with data processing using IBM SPSS version 22. The results of the study show that the application of government accounting standards and regional financial accounting systems can improve the quality of financial reports, but HR competencies can significantly reduce the quality of financial reports. SAP, regional financial accounting systems, and HR competencies can simultaneously significantly reduce the quality of financial reports at Puskesmas throughout Pekalongan Regency. The contribution given by the application of government accounting standards, regional financial accounting systems and HR competencies in improving the quality of financial reports is High.